2021
DOI: 10.1021/acs.langmuir.1c01734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ethylene Vinyl Acetate Copolymer on the Induction of Cyclopentane Hydrate in a Water-in-Waxy Oil Emulsion System

Abstract: In this paper, the effect of the ethylene vinyl acetate (EVA) copolymer, commonly used in improving rheological behavior of waxy oil, is introduced to investigate its effect on the formation of cyclopentane hydrate in a water-in-waxy oil emulsion system. The wax content studied shows a negative effect on the formation of hydrate by elongating its induction time. Besides, the EVA copolymer is found to elongate the induction time of cyclopentane hydrate through the cocrystallization effect with wax molecules adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Additionally, the PMSQ microspheres were also compared to EVA and PVP, as the representatives of commercial PPDs and hydrate inhibitors, respectively, as illustrated in Figure . The results indicated that the addition of EVA alone had no evident inhibition effect on the hydrate formation in the 5 wt % wax-containing oil–water system without the help of surfactants Span 80 . On the other hand, 1000 ppm of PVP almost failed to inhibit CP hydrate nucleation, due to only withstanding a subcooling degree less than 10 K. In contrast, for the oil–water system absent from wax, adding 1000 ppm PMSQ microspheres also evidently delayed the induction time but was not as strong as that for the waxy oil–water system.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, the PMSQ microspheres were also compared to EVA and PVP, as the representatives of commercial PPDs and hydrate inhibitors, respectively, as illustrated in Figure . The results indicated that the addition of EVA alone had no evident inhibition effect on the hydrate formation in the 5 wt % wax-containing oil–water system without the help of surfactants Span 80 . On the other hand, 1000 ppm of PVP almost failed to inhibit CP hydrate nucleation, due to only withstanding a subcooling degree less than 10 K. In contrast, for the oil–water system absent from wax, adding 1000 ppm PMSQ microspheres also evidently delayed the induction time but was not as strong as that for the waxy oil–water system.…”
Section: Resultsmentioning
confidence: 94%
“…The results indicated that the addition of EVA alone had no evident inhibition effect on the hydrate formation in the 5 wt % wax-containing oil−water system without the help of surfactants Span 80. 30 On the other hand, 1000 ppm of PVP almost failed to inhibit CP hydrate nucleation, due to only withstanding a subcooling degree less than 10 K. In contrast, for the oil−water system absent from wax, adding 1000 ppm PMSQ microspheres also evidently delayed the induction time but was not as strong as that for the waxy oil−water system. This reflected the inhibition synergistic effect of PMSQ and wax on the hydrate nucleation, meaning an optimistic application potential in the flow safety of the oil and gas field.…”
Section: Effect Of Pmsq Microspheres On Hydrate Induction Timementioning
confidence: 97%
See 1 more Smart Citation
“…Gas hydrates are molecular inclusion compounds that trap small gas molecules, such as CH 4 , C 2 H 6 , and CO 2 , within polyhedral hydrogen-bonded water cavities under a high pressure and a low temperature, and there are three types of gas hydrate structures, i.e., structure I (sI), structure II (sII), and structure H (sH), depending on the type of guest molecule. Although gas hydrates are well-known as a new clean energy resource, studies on the prevention of nucleation and adhesion of hydrate particles from the surface of a specific substrate have recently attracted extensive attention in academia and industry to address issues, such as pipeline flow safety, because undesired hydrates adhered toughly on the oil and gas pipes generally lead to severe blockage or even shutdown of the pipeline system .…”
Section: Introductionmentioning
confidence: 99%
“…(a) Many scholars have published microimages of wax crystal morphology. However, especially under specific conditions or the action of PPDs, the development of wax crystal morphology is complex, and its contribution to changes in system fluidity is not completely clear. (b) An increasing number of scholars have observed that, in addition to the influence of wax crystal morphology, the interaction between wax crystals is critical in determining macroscopic rheological properties of oil. However, current research methods cannot effectively explore these properties and mechanics performance. (c) Scholars pay much attention to the simultaneous measurement of waxy crude oil rheology and microstructure.…”
Section: Introductionmentioning
confidence: 99%